2016
DOI: 10.1016/j.jth.2015.08.007
|View full text |Cite
|
Sign up to set email alerts
|

The association of trip distance with walking to reach public transit: Data from the California Household Travel Survey

Abstract: Introduction Use of public transit is cited as a way to help individuals incorporate regular physical activity into their day. As a novel research topic, however, there is much we do not know. The aim of this analysis was to identify the correlation between distance to a transit stop and the probability it will be accessed by walking. We also sought to understand if this relation was moderated by trip, personal or household factors. Methods Data from the 2012 California Household Travel Survey was used for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 18 publications
1
37
0
Order By: Relevance
“…Moreover, for transit stations in low-income areas, policymakers should consider expand the catchment areas for the walking access to serve those moving farther because of the increased housing prices. 1 This study found that high population density areas were positively associated with walking to/from transit to work in both 2009 and 2017, which is consistent with previous studies. 10 High-density areas may feature mixed land use and sufficient pedestrian-friendly infrastructure, 24,25 providing a walker-friendly environment with multiple daily destinations to support walking behaviors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, for transit stations in low-income areas, policymakers should consider expand the catchment areas for the walking access to serve those moving farther because of the increased housing prices. 1 This study found that high population density areas were positively associated with walking to/from transit to work in both 2009 and 2017, which is consistent with previous studies. 10 High-density areas may feature mixed land use and sufficient pedestrian-friendly infrastructure, 24,25 providing a walker-friendly environment with multiple daily destinations to support walking behaviors.…”
Section: Discussionsupporting
confidence: 92%
“…Public transportation has identified as the means of integrating transit-related physical activity into regular life. 1 Instead of providing point-to-point travel service, taking public transit requires users to take the trip to the transit station and the trip to the destination. 2,3 Therefore, the additional trips provide travelers the opportunity to achieve at least 30 minutes of physical activity per day to meet the recommended guidelines of 150 minutes of physical activity per week.…”
mentioning
confidence: 99%
“…Previous studies have shown that the landscape of a living environment, availability of good footpaths, daily means of transportation, accessibility to shops, and altitude can influence the time that people spend for walking [15–19]. Based on this consideration, we used the number of rail stations per 100 km 2 of habitable land ("stations"), standard-vehicle usage ("standard-vehicle"), light-vehicle usage ("light-vehicle"), and steepness of habitable land ("slope") as variables for which data aggregated per prefecture was available.…”
Section: Methodsmentioning
confidence: 99%
“…Among these measures there is a focus on walking distance [1][2][3]. Distance to transit together with density, diversity, (street) design, and distance to destination are an urban form attributes known as 5 D's used when verify the effect of built environment on walking and cycling [4].…”
Section: Introductionmentioning
confidence: 99%